IR-spectrum of monometallic copper(II) halogenide complexes with 1-tert-butyl-1,2,4-tria zole: experimental and quantum chemical studies - Saparova, Djennet S.; Bogatikov, Andrey N.; Matulis, Vadim E.; Degtyarik, Mikhail M. (Journal of the Belarusian State University. Chemistry, 2019)
The crystalline complexes CuL2X2 and CuL4X2 , where X = Cl or X = Br were synthesized by the interaction of copper(II) chloride or bromide with 1-tert-butyl-1,2,4-triazole (L) in water or organic solvents. The structure of metal complexes have been studied by elemental analysis, X-ray analysis and IR-spectroscopy in the medium (4000 –500 cm –1 ) and long-wavelength (400–50 cm –1 ) regions. Quantum chemical calculations of the vibrational spectra of the CuL2Cl2 and CuL4Cl2 complexes have been carried out to perform the assignment of the signals in the IR-spectra. It is shown that the polymer structure of CuL2X2 complexes is formed due to bridging of one of their halide ions. In the CuL4X2 complexes, the halide ions and 1-tert-butyl-1,2,4-triazole form an island type structure. In all metal complexes 1-tert-butyl-1,2,4-triazole is coordinated by N(4) atom of heterocycle.